Nuclear transfer: Progress and quandaries - Zhou Qi; Jouneau Alice; Li Ziyi; Li Xuemei; Renard Jean-Paul (BMC, 2003)
Abstract Cloning mammals by nuclear transfer is a powerful technique that is quickly advancing the development of genetically defined animal models. However, the overall efficiency of nuclear transfer is still very low and several hurdles remain before the power of this technique will be fully harnessed. Among these hurdles include an incomplete understanding of biologic processes that control epigenetic reprogramming of the donor genome following nuclear transfer. Incomplete epigenetic reprogramming is considered the major cause of the developmental failure of cloned embryos and is frequently associated with the disregulation of specific genes. At present, little is known about the developmental mechanism of reconstructed embryos. Therefore, screening strategies to design nuclear transfer protocols that will mimic the epigenetic remodeling occurring in normal embryos and identifying molecular parameters that can assess the developmental potential of pre-implantation embryos are becoming increasingly important. A crucial need at present is to understand the molecular events required for efficient reprogramming of donor genomes after nuclear transfer. This knowledge will help to identify the molecular basis of developmental defects seen in cloned embryos and provide methods for circumventing such problems associated with cloning the future application of this technology.